1982
DOI: 10.1099/0022-1317-60-2-225
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Herpes Simplex Virus in Congenitally Athymic Mice: the Relative Roles of Cell-mediated and Humoral Immunity

Abstract: SUMMARYAthymic nude (nu/nu) mice were inoculated in the ear pinna with 104 p.f.u, herpes simplex virus type 1 (strain SC 16). Initially, the virus was observed to replicate in the pinna, spreading via a neurological route to the dorsal root ganglia, spinal cord, brain and adrenal glands. Following the transfer of lymphoid cells from day 7 herpesvirus-infected hairy immunocompetent donors into infected nude mice, virus was not isolated from the pinna and nervous system of the majority of the mice. The passive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 23 publications
4
51
0
Order By: Relevance
“…However, later spread to other parts of the nervous system is likely to involve extracellular virus (Hill, 1987) which could be neutralized by antibodies. Passively transferred anti-HSV-1 antibodies, given 3 days after inoculation of the pinna were found to reduce the amount of virus reaching the ganglion and spinal cord but did not alter the amount of virus at the inoculation site (Kapoor et al, 1982).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, later spread to other parts of the nervous system is likely to involve extracellular virus (Hill, 1987) which could be neutralized by antibodies. Passively transferred anti-HSV-1 antibodies, given 3 days after inoculation of the pinna were found to reduce the amount of virus reaching the ganglion and spinal cord but did not alter the amount of virus at the inoculation site (Kapoor et al, 1982).…”
Section: Discussionmentioning
confidence: 87%
“…These clinical observations were supported by the similarity in the two groups of timing and incidence of virus isolation from eye washings and virus antigens in corneal epithelial sheets. Others have reported that passive immunization does not affect titres of virus at the inoculation site during primary infection of the eye (Lausch et al, 1989) or skin (Kapoor et aL, 1982). In contrast, if mice are actively immunized against HSV-1 some time before inoculation of the cornea virus is rapidly cleared from the tears (Tullo et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Such differences in tissue sensitivities to interferon are apparent in the case of other virus infections in mice (Dandoy et al, 1982). Experiments with nude and immunocompetent mice have revealed that the route of inoculation with virus also has an effect on the outcome and host susceptibility to infection (Kapoor et al, 1982). The inference is that different mechanisms of protection, either cell-mediated or humoral, are preferentially induced according to the site of virus inoculation and that the potential of…”
Section: Discussionmentioning
confidence: 99%
“…Both nonspecific (mediated by macrophages and natural killer cells) and specific immune responses (mediated by B and T cells) have been implicated as important host defenses against HSV-1 infections. [48][49][50][51][52][53] The relative value of each of these defense mechanisms varies significantly according to the genetic background of the host 54,55 and the route of viral inoculation.…”
Section: Lytic Infection Vs Latencymentioning
confidence: 99%